The Mitochondrial Genome and a 60-kb Nuclear DNA Segment from Naegleria fowleri, the Causative Agent of Primary Amoebic Meningoencephalitis - Herman, Emily K. (2013)
Naegleria fowleri is a unicellular eukaryote causing primary amoebic meningoencephalitis, a neuropathic disease killing 99% of those infected, usually within 7–14 days. N. fowleri is found globally in regions including the US and Australia. The genome of the related non-pathogenic species Naegleria gruberi has been sequenced, but the genetic basis for N. fowleri pathogenicity is unclear. To generate such insight, we sequenced and assembled the mitochondrial genome and a 60-kb segment of nuclear genome from N. fowleri. The mitochondrial genome is highly similar to its counterpart in N. gruberi in gene complement and organization, while distinct lack of synteny is observed for the nuclear segments. Even in this short (60-kb) segment, we identified examples of potential factors for pathogenesis, including ten novel N. fowleri-specific genes. We also identified a homologue of cathepsin B; proteases proposed to be involved in the pathogenesis of diverse eukaryotic pathogens, including N. fowleri. Finally, we demonstrate a likely case of horizontal gene transfer between N. fowleri and two unrelated amoebae, one of which causes granulomatous amoebic encephalitis. This initial look into the N. fowleri nuclear genome has revealed several examples of potential pathogenesis factors, improving our understanding of a neglected pathogen of increasing global importance.